Sustained Presence of Cutaneous Leishmaniasis in Urban Manaus, the Largest Human Settlement in the Amazon - Benício, Ednelza (Am J Trop Med Hyg, 2015)
The Amazon is responsible for approximately 40% of the American tegumentary leishmaniasis (ATL) in Brazil. Herein the sustained presence of ATL in Manaus, the largest settlement in the Amazon, was investigated. Records of notification of historic cases, and data from cases prospectively enrolled in the Tropical Medicine Foundation of the Amazonas State were used. Geographic coordinates of prospective patients' living sites were used to detect inner-city clusters of ATL. Infecting Leishmania species was determined by polymerase chain reaction. Among prospectively enrolled subjects, 94.8% were infected with Leishmania (Viannia) guyanensis, 76.7% were male, 30.2% were 0–20 years old, and 69.8% had an urban residence. Historic cases showed a profile similar to that of prospectively enrolled subjects. Several clusters of ATL, widely distributed within the city of Manaus, could be detected. In conclusion, there was a high frequency of disease in young age groups and cases clustered in urban neighborhoods. It cannot be determined from these data whether transmission of these cases occurred within or outside the city of Manaus.